Sentiment Analysis about Electric Motorbikes in Indonesia Using Twitter Data - Irawati, Desrina Yusi; Bellanov, Agrienta; Damayanti, Florencia Agatha (Spektrum Industri, 2024)
Along with the rapid development of technology, various types of transportation have experienced increased innovation in shapes, colours,models, and even engines. However, one thing that needs special attention is the number of pollutants or emissions released by vehicles. One effort to reduce emissions is increasing the production of Battery-Based Electric Motorized Vehicles. Battery-based electric vehicles developed in Indonesia include electric cars and electric motorcycles. Among these types of electric vehicles, Indonesian society widely adopts electric motorcycles. However, sales of electric motorbikes were only 15 thousand units, lower than sales of petrol motorbikes which reached 5 million units. This study contributes to understanding further how the community responds to electric motorcycles in detail through sentiment analysis on social media data. Consumer acceptance of electric motorcycles can be seen from the numerous active Twitter users in Indonesia who provide positive and negative comments on the presence of electric motorcycles. Text information based on public comments in Indonesia via Twitter is collected using Sentiment Analysis in R Studio. Twitter comments will be classified into positive, negative, and neutral groups. The results show 63% positive, 21% unfavourable, and 14% neutral opinions. This condition means that Indonesian society accepts and has a supportive opinion of the presence of electric motorcycles. The government and entrepreneurs can use this information to create electric motorcycles that align with the community's preferences.